Total Flavonoid and Tannin Content in Pumpkin Stem Extract (Cucurbita moschata) - Vadillah Vadillah; Sutrisnawati Sutrisnawati; Manap Trianto; Fatmah Dhafir; Zulaikhah Dwi Jayanti; Masrianih Masrianih (Biology, Medicine, & Natural Product Chemistry, 2026)
Cucurbita moschata is a medicinal plant that possesses various pharmacological properties, including antidiabetic, antifungal, antibacterial, anti-inflammatory, and antioxidant activities, which are associated with its bioactive compound content. One plant part that has been relatively underutilized is the pumpkin stem, although it has the potential to contain secondary metabolites such as flavonoids and tannins. This study aimed to identify and determine the levels of bioactive compounds in pumpkin stem extract based on stem maturity stages, namely young stems and mature stems, using both qualitative and quantitative methods. Qualitative analysis was conducted through phytochemical screening using color reaction methods with specific reagents to detect flavonoids and tannins. Quantitative analysis was performed using UV-Vis spectrophotometry based on standard calibration curves. The results showed that pumpkin stem extract tested positive for both flavonoids and tannins. Quantitative analysis indicated that the flavonoid content in young stems was 7.22, which was higher than in mature stems (3.00). In contrast, tannin content was higher in mature stems (9.03) compared to young stems (5.02). These differences indicate that flavonoids are more dominant in young tissues with active metabolic activity, whereas tannins tend to accumulate in mature tissues as part of plant defense mechanisms. Based on these findings, it can be concluded that pumpkin stem extract contains flavonoid and tannin compounds with varying levels depending on stem maturity, suggesting its potential as a natural source of antioxidants.